Literature, Religion, and the Evolution of Culture, 1660-1780 - Weinbrot, Howard D. (Book collections on Project MUSE., 2013)
This book chronicles changes in contentious politics and religion and their varied representations in British letters from the mid-seventeenth to the late eighteenth century. An uncertain trend toward tolerance and away from painful discord significantly influenced authors who reflected on and enhanced germane aspects of British literary and intellectual life. The movement was stymied during the painful Gordon Riots in June 1780, from which Britain needed to repair itself. The author's interdisciplinary study considers sermons, satire, political and religious polemic, Anglo-French relations, biblical and theological commentary, Methodism, legal history, and the novel. The author analyzes the texts and contexts of several major and minor authors, including Daniel Defoe, Charles Dickens, Olaudah Equiano, Maria De Fleury, Lord George Gordon, Nathaniel Lancaster, Henry Sacheverell, Tobias Smollett, and Edward Synge.